Proposal of compact multimode interference optical modulator with high extinction ratio. (1st August 2022) - Kanesaka, Yuhei; Arakawa, Taro
Abstract: We proposed a compact 1 × 1 multimode interference (MMI) optical modulator with a high extinction ratio. A triply coupled quantum well structure is designed for the core layer for the enhancement of the quantum-confined Stark effect, and the MMI waveguide with isolation trenches is symmetrically designed. The length of the MMI modulator is reduced by 30%, and the wavelength dependence was reduced compared with that observed in the previously reported MMI modulator. Owing to both the electroabsorption effect and the electric-field induced refractive index change in a multiple-quantum-well core layer, the extinction ratio is expected to be approximately 45 dB at an operating voltage of 3.3 V.